Behaviour of 125I-fibrinogen and 131I-albumin in experimental galactosamine-induced hepatitis. Issue 7 (July 1977) - Mahn, I; Merkel, H; Sattler, E L; Müller-Berghaus, G
Abstract : The turnover of 125I-labelled fibrinogen and 131I-labelled albumin was studied in the course of galactosamine-induced hepatitis in rabbits. In addition to galactosamine, some animals were treated with epsilon-aminocaproic acid (EACA) to inhibit the activation of the fibrinolytic system. The infusion of galactosamine and EACA caused generation of fibrin-rich microclots in the renal glomerular capillaries in seven out of 12 rabbits. Correspondingly, the incorporation of 125I-radioactivity into liver, spleen, and kidneys was pronounced in galactosamine- and EACA-treated rabbits compared with control animals treated with EACA. An acceleration of the 125I-fibrinogen elimination from the plasma was observed between eight and 12 hours after the start of the galactosamine infusion. The administration of heparin in addition to galactosamine and EACA prevented the occurrence of intravascular coagulation, but shortened the survival times of the animals because of bleeding into visceral organs. The elimination of 131I-albumin in plasma as well as the distribution of 131I-radioactivity in organs were similar in all the rabbits independent of the treatment with galactosamine, EACA, or heparin. The experiments indicate that, in addition to diminished synthesis of coagulation factors, disseminated intravascular coagulation is involved in galactosamine-induced hepatitis and contributes to the haemostatic disorder.